Analisis Sebaran Spasial Kerentanan Longsor Sebagai Upaya Mitigasi Bencana di Kecamatan Berastagi Kabupaten Karo Provinsi Sumatera Utara - Dinda Ayu Pertiwi Sitorus; Slamet Bejo; Said Muzambiq (Fakultas Teknik, 2021)
Kabupaten Karo has several areas that have the potential to occurrence of a landslide.Therefore, the mitigation of landslide disaster is very important, it has long-term negative impacts on humanity and the environment. This study attempts to analyze the distribution of vulnerability landslides in Berastagi mitigation and management and provide the right environment. The causes of a movement occur landslides in Berastagi is the state of a steep slope around 35, 55 % - percent of lithological building materials / unstable material among other volcanic breccias and, riodasit tufa and the factor triggering rainfall andinfiltration water . The research method was descriptive , whereas scoring with Shapefile (SHP) data in 2019 was based on the 2004 Puslittanak. The results of the field are the weightings of the respective parameter with overlay uses arcgis 10.6 software. The result showed that the DouluVillage, SempaJaya Village, Raya Village, as well as Tambak Lau Mulgap II in the Berastagi District have a high vulnerability to landslides. Thus, recommendations for mitigation of calamity , by revegetation erosion including planting crops.